Painting depicts a procession with the palkhi (palanquin) of Bhandaprasad - Temples of India Project Team (Jio Institute, 2024)
The episode in the eighth oval painting (in clockwise order), in the lower/outer circle in the ceiling of the mandapa (pillared hall), oval painting deviates from the usual stories of the Dada Guru but holds importance in the context of the temple. The painting depicts a procession, the palkhi (palanquin) of Bhandaprasad, the Sethia credited with the patronization of the Bhandasar Temple. The procession shown in the painting is grand, with Bhandaprasad being carried in a palkhi by four men and accompanied by foot soldiers, cavalry, elephants, and horse riders. The procession is passing by a Rajasthani haveli (mansion). The inscription reads, ‘Shri Bhandaprasad ri Palkhi.’